The Impact of Excluding Nonrandomized Studies From Systematic Reviews in Rare Diseases: “The Example of Meta-Analyses Evaluating the Efficacy and Safety of Enzyme Replacement Therapy in Patients With Mucopolysaccharidosis” - Sampayo-Cordero, Miguel; Miguel-Huguet, Bernat; Malfettone, Andrea; Pérez-García, José Manuel; Llombart-Cussac, Antonio; Cortés, Javier; Pardo, Almudena; Pérez-López, Jordi (Frontiers in Molecular Biosciences, 2021)
Abstract Non-randomized studies are usually excluded from systematic reviews. This could lead to loss of a great amount of information in rare disease. We aim to explore the impact of excluding non-randomized studies on the generalizability of meta-analyses results in mucopolysaccharidosis disease. A comprehensive search of systematic reviews in mucopolysaccharidosis patients up to May 2020 was carried out (CRD42020191217). The primary endpoint was the rate of patients excluded from systematic reviews if only randomized studies were considered. Secondary outcomes included the differences in patient and study characteristics between randomized and non-randomized studies, the methods used to combine data from studies with different designs, and the number of patients excluded from systematic reviews if case reports were not considered. More than 50% of the patients analyzed have been recruited in non-randomized studies. Patient characteristics, duration of follow-up, and the clinical outcomes evaluated differ between the randomized and non-randomized studies. There are feasible strategies to combine the data from different randomized and non-randomized designs. The analyses suggest the relevance of including case reports in the systematic reviews, since the smaller the number of patients in the reference population, the larger the selection bias associated to excluding case reports. Our results recommend including non-randomized studies in the systematic reviews of mucopolysaccharidosis to increase the representativeness of the results and to avoid a selection bias. The recommendations obtained from this study should be considered when conducting systematic reviews on rare diseases.